Fuzzy distributed artificial intelligence systems - Nakamiti, G. [UNESP]; Freitas, R. [UNESP]; Prado, J. [UNESP]; Gomide, F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1994)
In this paper, we introduce a DAI approach called hereinafter Fuzzy Distributed Artificial Intelligence (FDAI). Through the use of fuzzy logic, we have been able to develop mechanisms that we feel may effectively improve current DAI systems, giving much more flexibility and providing the subsidies which a formal theory can bring. The appropriateness of the FDAI approach is explored in an important application, a fuzzy distributed traffic-light control system, where we have been able to aggregate and study several issues concerned with fuzzy and distributed artificial intelligence. We also present a number of current research directions necessary to develop the FDAI approach more fully.
Keywords: Artificial intelligence; Computer systems; Distributed parameter control systems; Formal logic; Knowledge representation; Traffic control; Traffic signals; Fuzzy distributed artificial intelligence systems; Fuzzy systems; Traffic light control; Fuzzy sets